Corporate Governance : A North American Perspective - World Bank (Washington, DC, 2012)
The recent wave of US corporate governance failures prompted a round of legal and regulatory reform which has attracted worldwide attention. The author's essay puts the debate into a wider context for the US. The missing link here is the rights of the shareholders in the US who have comparatively weaker rights than shareholders in some other countries, thereby making it difficult for shareholders to hold boards to account without prohibitive cost and effort. The message is that law and regulation must be seen to complement, and to facilitate market action, but not to substitute for it. That is a valuable insight from the author who is one of the world's most experienced and thoughtful corporate governance practitioners.